Analisis Faktor-Faktor Penerimaan SiakadCloud Menggunakan Technology Acceptance Model (TAM) di IAIN Manado (Studi Kasus Dosen dan Mahasiswa) - Nur Fadli Utomo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
This study aims to determine and evaluate the extent of the implementation of SiakadCloud at IAIN Manado and the various factors that influence it. SiakadCloud has been integrated with the academic activities of IAIN Manado for approximately 3 years and has experienced various kinds of problems in it. The variable user acceptance is the main dependent variable of this study and the external variables that the researchers observed were two variables, namely system quality and user experience. This research method is descriptive quantitative with Path Analysis method to analyze the influence path between variables. The sampling method used random sampling for student respondents and convenience sampling for lecturer respondents. The total sample of this study amounted to 348 respondents, which were divided into 300 respondents from student respondents and 48 respondents from lecturers. Conducting research during the odd semester 2021/2022 at IAIN Manado. The results showed that about 55% of lecturer respondents were quite familiar with SiakadCloud and had used it for a long time and planned to continue it and the rest were still adjusting and using SiakadCloud to complete their duties as lecturers. For student respondents, about 80% have used Siakadcloud for academic administration processes every semester and to check class schedules and attendance and the rest are still in the adjustment period. The hypothesis that external variables, namely system quality and user experience, affect user acceptance, is accepted with an average percentage of 27.95%, the percentage is simultaneously the system quality variable, user experience, and everyday user attitudes, and the rest is influenced by other variables not included in this study.